Prevalence of Dual-Positivity for Both Hepatitis B e Antigen and Hepatitis B e Antibody Among Hospitalized Patients with Chronic Hepatitis B Virus Infection - Liu Y (International Journal of General Medicine, 2021)
Yuanyuan Liu,1,2 Songmei He,2 Sichun Yin,2 Qingyang Zhong,2 Jianbo Zhong,2 Xiaoyong Zhang,1 Rong Fan,1 Jinlin Hou1,3 1Department of Infectious Diseases, State Key Laboratory of Organ Failure Research, Guangdong Provincial Key Laboratory of Viral Hepatitis Research, Nanfang Hospital, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 2Department of Infectious Diseases, Dongguan People’s Hospital, Dongguan, Guangdong, People’s Republic of China; 3Hepatology Unit, Shenzhen Hospital, Southern Medical University, Shenzhen, Guangdong, People’s Republic of ChinaCorrespondence: Jinlin HouDepartment of Infectious Diseases, State Key Laboratory of Organ Failure Research, Guangdong Provincial Key Laboratory of Viral Hepatitis Research, Nanfang Hospital, Southern Medical University, Guangzhou, Guangdong, People’s Republic of ChinaTel +86 20 61641941Fax +86 20 62786530Email jlhousmu@163.comObjective: The detection of dual-positivity for both hepatitis B e antigen (HBeAg) and hepatitis B e antibody (anti-HBe) is not typically performed for patients with hepatitis B virus (HBV). This cross-sectional study was designed to figure out the prevalence of dual-positivity for both HBeAg and anti-HBe (DEP) among hospitalized patients with chronic hepatitis B virus infection (C-HBVI).Patients and Methods: Data from 2820 cases with C-HBVI from two centers in China were retrospectively analyzed. Univariate and multivariate logistic regression analyses were undertaken to identify the risk factors for liver fibrosis (LF) and acute-on-chronic liver failure (ACLF).Results: There were 165 (5.9%), 688, and 1903 patients in DEP, HBeAg+/anti-HBe-, and HBeAg-/anti-HBe+ groups, respectively. The DEP patients’ median age was 43.6 years old and 71.5% of them were male. They had higher levels of alanine transaminase, total bilirubin, and international normalized ratio. Furthermore, DEP cases had a higher proportion of liver cirrhosis, and it was associated with non-invasive testing of LF, including aspartate transaminase (AST)-to-platelet ratio index (APRI) > 1.5 (odds ratio (OR) = 1.96, 95% confidence interval (CI): 1.27– 3.03, P = 0.002) and fibrosis-4 (FIB-4) score > 1.45 (OR = 2.07, 95% CI: 1.28– 3.34, P = 0.003). DEP also contributed to the elevated risk of ACLF (OR = 4.80, 95% CI: 2.02– 11.39, P < 0.001).Conclusion: DEP cases are at higher risks of LF and ACLF than other patients with HBV infection. A fast diagnosis and an active monitoring of liver diseases for DEP patients are extremely vital.Keywords: hepatitis B e antigen, hepatitis B e antibody